The taste of the island. For a semiotics of Ichnusa beer - Sorrentino, Paolo (E|C, 2020)
The famous works by Floch (1997) and Landowski (2003) attest how culture and communication linked to the consumption of beer can be a good starting point for reflecting on the relationship between taste and politics. The opportunity to follow this path is offered by Ichnusa Beer and its Anima sarda commercial (2018). The film is a montage of faces, gestures, sounds, noises, bodies, landscapes that embody the spirit of the island. We would therefore like to proceed with the semiotic analysis of the commercial considering it as a case of translation of tradition (Sedda 2019), in which the oppositions between folklore / creativity, globality / locality, identity / otherness, taste / flavor are redefined in the plot of a common world. In conclusion, we would like to show not only how the narrative of the island defines the taste of beer, but also how the narrative of beer redefines the taste of the island (see Marrone 2014).